2018
DOI: 10.1111/imj.13952
|View full text |Cite
|
Sign up to set email alerts
|

How should procalcitonin and C‐reactive protein levels be interpreted in haemodialysis patients?

Abstract: We specified PCT and CRP cut-off values with high PPV and NPV for revealing the presence of bacterial infection and sepsis in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Our analysis showed that higher values for NLR and PLR in high (> 3 mg/L) hs-CRP level group than those in low (≤ 3 mg/L) level group in non-dialysis ESRD patients, is consistent with the result in HD patients [11]. Similar to hs-CRP, PCT and ferritin are also inflammatory markers [8,9]. Thus, it is reasonable to have the result that high hs-CRP level group has significantly higher values of PCT and ferritin compared to low hs-CRP level group in our current study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our analysis showed that higher values for NLR and PLR in high (> 3 mg/L) hs-CRP level group than those in low (≤ 3 mg/L) level group in non-dialysis ESRD patients, is consistent with the result in HD patients [11]. Similar to hs-CRP, PCT and ferritin are also inflammatory markers [8,9]. Thus, it is reasonable to have the result that high hs-CRP level group has significantly higher values of PCT and ferritin compared to low hs-CRP level group in our current study.…”
Section: Discussionsupporting
confidence: 86%
“…Inflammatory markers such as C-reactive protein (CRP), procalcitonin (PCT), and ferritin are widely used in ESRD [8][9][10]. However, those traditional biomarkers have their limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, PCT level kinetics and CRP level kinetics have become the focus of research efforts for identification and assessment of disease prognosis. 9,10 Under normal physiological conditions, the levels of serum PCT and CRP are very low, and are maintained at a relative equilibrium in the body. When sepsis is caused by an inflammatory stimulus due to pathogen infection, the levels of serum PCT and CRP increase rapidly due to the host response to infection.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of PCT, CRP and SAA have important clinical significance in the diagnosis and treatment of Sepsis and other infectious diseases. [5][6][7][8][9][10] Application value of PCT, hs-CRP and SAA detection SAA is one of the markers of inflammatory activity in the acute response phase, mainly produced by macrophages. 11 SAA has the characteristics of a low basal level and high induced expression, and it is produced in large quantities in the inflammatory acute response period.…”
Section: Discussionmentioning
confidence: 99%